Mobile learning for teacher professional learning: benefits, obstacles and issues - Peter Aubusson; Sandy Schuck; Kevin Burden (Association for Learning Technology, 2009)
This paper reflects on the role of mobile learning in teachers' professional learning. It argues that effective professional learning requires reflection and collaboration and that mobile learning is ideally suited to allow reflection-inaction and to capture the spontaneity of learning moments. The paper also argues for the value of collaborations between teachers and students in professional learning. It suggests that authentic artefacts and anecdotes, captured through mobile technologies, can enable the sharing, analysis and synthesis of classroom experiences by teachers and students. Such analysis and synthesis helps to encourage collaborative reflective practice and is likely to improve teacher and student learning as a result. Ethical issues that might arise through using mobile technologies in this way are also discussed. Teacher voice is presented to indicate the range of views about mobile learning and to indicate current practices. Practical, school systemic, attitudinal and ethical factors may inhibit mobile technology adoption; these factors need to be researched and addressed to realise the potential of teacher mobile professional learning.